An injectable hydrogel with self-healing and adhesive properties and its preparation method and application

By combining the negatively charged component A and the positively charged component B in the injectable hydrogel to form a three-dimensional network structure of secondary bonds such as hydrogen bonds through the interaction of positive and negative charges, the problem of existing hydrogels is solved. deficiencies in self-healing properties, adhesion and antibacterial properties, achieving an efficient and simple preparation process and good biocompatibility.

CN115850728BActive Publication Date: 2025-01-21TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111120164.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-24
Publication Date
2025-01-21
Estimated Expiration
2041-09-24

AI Technical Summary

Technical Problem

Existing injectable hydrogels have poor performance in self-healing properties, adhesion and antibacterial properties, and the preparation process is complicated. The reaction needs to be carried out in an organic solvent, so the gel molding is slow.

Method used

By interacting the negatively charged component A and the positively charged component B through positive and negative charges, secondary bonds such as hydrogen bonds are formed between the polymer chains, and a three-dimensional network structure of the hydrogel is constructed. Component A is obtained by reacting natural polymers, polyethylene glycol and negatively charged nanoclay, while component B is obtained by reacting polyacrylamide, dopamine hydrochloride, calcium chloride and antibacterial ingredients.

Benefits of technology

It improves the self-healing properties, adhesion and antibacterial properties of hydrogels, and simplifies the preparation process. It can quickly generate hydrogels without the need for organic solvents, has good biocompatibility and promotes cell growth. The role of proliferation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115850728B_ABST
    Figure CN115850728B_ABST
Patent Text Reader

Abstract

The present invention discloses an injectable hydrogel with self-healing and adhesive properties, wherein the injectable hydrogel material is generated by the interaction between component A and component B through positive and negative charges; wherein component A is a negatively charged stable solution obtained by reacting natural polymers, polyethylene glycol and negatively charged nanoclay; and component B is a positively charged stable solution obtained by reacting polyacrylamide with dopamine hydrochloride, calcium chloride and antibacterial components. Secondary bonds such as hydrogen bonds are formed between polymer chains in the hydrogel, which has self-healing properties and promotes coagulation function, and can shorten the blood coagulation time by 50%; at the same time, it also has good strong adhesion and underwater adhesion performance, injectability, guaranteed biocompatibility and safety, and tensile elasticity of up to 300%, and has good application prospects in the production of wound dressings and cell tissue adhesives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and more specifically, to an injectable hydrogel material with self-healing and adhesive properties, and a preparation method and application thereof. Background Art

[0002] Hydrogel is a hydrophilic material with a three-dimensional network structure formed by a polymer and a large amount of water. Due to its structural characteristics similar to human muscle, skin and other tissues, hydrogel has received great attention in the field of biomedical materials. For example, tissue engineering scaffolds, drug carriers, electronic skin, sensors, wound dressings, etc. Among them, injectable hydrogels have become one of the current research hotspots because they can be implanted into the body through painless minimally invasive surgery and have great product development value. Reis et al. prepared poly (N-isopropylacrylamide)-g-methylcellulose (PNIPAAm-g-MC) injectable hydrogel using thermal phase change, which can be used in cartilage tissue engineering (J Biom 2011, 98 (4), 596–603.). Zhang Yan et al. disclosed a PEG-PCL injectable thermosensitive physical hydrogel, which is in a flowable sol state at room temperature and below, and in a gel state at 37°C. It can be used in drug delivery, cell encapsulation and tissue repair.

[0003] Natural polymers are ideal raw materials for injectable hydrogels, mainly including polypeptides, gelatin, zein, silk protein, polysaccharides, cellulose, hyaluronic acid, agar, carrageenan, alginate, etc., with strong hydrophilicity, low antigenicity, high biocompatibility, etc., and are widely used in simulating the microenvironment of human tissues, such as regulating cell adhesion, migration and tissue regeneration. Therefore, the injectable hydrogel formed by natural polymers and other polymers through physical (such as ions, hydrogen bonds, electrostatic interactions, etc.) or chemical cross-linking (covalent bonds, dynamic covalent bonds, coordination bonds, etc.) has great application prospects in the field of biomedical materials. Chinese patent CN112316214A discloses a recombinant collagen injectable hydrogel, in which hydroxyphenylpropionic acid / recombinant collagen forms a conjugate under the action of an activator, and after separation and purification, it reacts with hydrogen peroxide and peroxidase to form a hydrogel, which can be used in the fields of soft tissue filling, drug delivery and medical plastic surgery. However, the preparation process is complicated, the reaction needs to be carried out in an organic solvent and the gel formation is slow, resulting in the hydrogel having disadvantages such as poor self-healing performance, adhesion and antibacterial properties.

[0004] Therefore, there is a need to provide an injectable hydrogel with excellent self-healing properties, adhesion and antibacterial properties. Summary of the invention

[0005] One object of the present invention is to provide an injectable hydrogel with self-healing and adhesive properties. The injectable hydrogel is composed of a negatively charged component A and a positively charged component B. Through the interaction of positive and negative charges, secondary bonds such as hydrogen bonds are formed between polymer chains, thereby constructing a three-dimensional network structure of the hydrogel, giving the hydrogel material strong underwater adhesion, self-healing properties, antibacterial properties, and coagulation-promoting properties.

[0006] Another object of the present invention is to provide a method for preparing an injectable hydrogel having self-healing ability and adhesiveness.

[0007] Another object of the present invention is to provide an application of an injectable hydrogel having self-healing ability and adhesiveness.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] An injectable hydrogel with self-healing and adhesive properties, wherein the injectable hydrogel material is generated by the interaction between component A and component B through positive and negative charges;

[0010] The component A is a negatively charged stable solution obtained by reacting natural polymers, polyethylene glycol and negatively charged nanoclay; the component B is a positively charged stable solution obtained by reacting polyacrylamide with dopamine hydrochloride, calcium chloride and antibacterial ingredients.

[0011] Preferably, the volume ratio of component A to component B is 2:1 to 1:2.

[0012] The A component and the B component of the injectable hydrogel in the present invention have opposite charges. Through the interaction of positive and negative charges, secondary bonds such as hydrogen bonds are formed between the polymer molecular chains in the two components, and a three-dimensional network structure of a composite hydrogel is constructed, which gives the hydrogel strong underwater adhesion, self-healing properties, antibacterial properties and coagulation-promoting properties. At the same time, the raw materials of the injectable hydrogel are natural polymers, polyethylene glycol, polyacrylamide, polydopamine, etc., with good biosafety and cell compatibility, and can promote cell proliferation. Therefore, it can be used to make biomedical products such as cell tissue adhesives and gel wound dressings.

[0013] In addition, the injectable gel in the present invention includes component A and component B, both of which are stable solutions. During use, a double injection process can be used to generate hydrogel in situ. The required syringe inner diameter is smaller than that when the hydrogel is directly injected, and a needle syringe with an inner diameter of 0.45 mm can meet the requirements.

[0014] Preferably, the preparation process of the A component comprises: heating and dissolving the natural polymer and polyethylene glycol, mixing and dissolving them in pure water, and then adding negatively charged nanoclay and mixing them to obtain the A component.

[0015] Preferably, the heating and dissolving process is carried out in a water bath at 50-100°C.

[0016] Preferably, the natural polymer is selected from one or more of gelatin, hyaluronic acid, silk fibroin, zein, agar, carrageenan, and alginate; the natural polymer material can ensure the biosafety and biocompatibility of the gel.

[0017] Preferably, the number average molecular weight of the polyethylene glycol is 0.8 to 100,000;

[0018] Preferably, the types of the nanoclay include but are not limited to attapulgite nanoclay, halloysite nanoclay and hydrophilic bentonite, etc., and the particle size of the nanoclay is 1 to 100 nm.

[0019] Preferably, in the component A, the mass proportion of natural polymer is 0.1-5wt%, the mass proportion of polyethylene glycol is 0.1-5wt%, and the mass proportion of negatively charged nanoclay is 1-10wt%.

[0020] Preferably, the preparation process of the B component includes: dissolving polyacrylamide in pure water, adding dopamine hydrochloride, calcium chloride and antibacterial components, and mixing to obtain the B component.

[0021] Preferably, the molecular weight of the polyacrylamide is 2 million to 14 million.

[0022] Preferably, the antibacterial component is selected from one or more of bacitracin, bacitracin zinc, nisin, chitosan, ZnCl2, AgNO3, silver nanoparticles, and ZnO.

[0023] Preferably, the mass proportion of polyacrylamide in component B is 1-5wt%, and the mass ratio of polyacrylamide, dopamine hydrochloride and calcium chloride is 1:(0.01-1):(0.005-0.02);

[0024] Further preferably, the mass ratio of the polyacrylamide, dopamine hydrochloride and calcium chloride includes but is not limited to 1:(0.01-0.08):(0.005-0.02), 1:(0.01-0.06):(0.005-0.015), 1:(0.01-0.05):(0.005-0.01) or 1:(0.01-0.05):(0.005-0.015), etc.

[0025] Preferably, the mass concentration of the antibacterial component in component B includes but is not limited to 20 μg / mL to 200 μg / mL, 50 μg / mL to 90 μg / mL, 60 μg / mL to 80 μg / mL or 70 μg / mL.

[0026] The present invention also provides a method for preparing the above-mentioned injectable hydrogel with self-healing and adhesive properties, comprising the following steps:

[0027] (1) heating and dissolving the natural polymer and polyethylene glycol, mixing and dissolving them in pure water, then adding negatively charged nanoclay, and mixing them well to obtain component A;

[0028] (2) dissolving polyacrylamide in pure water, adding dopamine hydrochloride, calcium chloride and antibacterial components, and mixing well to obtain component B;

[0029] (3) Component A and component B are mixed in proportion, shaken, and cured to obtain an injectable hydrogel material.

[0030] The preparation method of the hydrogel in the present invention is simple and easy, and both component A and component B are stable solutions and easy to store. When used, the hydrogel can be quickly generated in situ by simultaneous injection of the two components, and the use process is convenient and easy to operate.

[0031] The present invention also provides the application of the injectable hydrogel having self-healing and adhesive properties.

[0032] The above-mentioned hydrogel has good injectability, strong underwater adhesion, excellent self-healing performance, good antibacterial properties, and the ability to promote coagulation and wound healing, cell proliferation, etc. Therefore, it has good application prospects in the preparation of wound dressings and cell tissue adhesives.

[0033] The beneficial effects of the present invention are as follows:

[0034] The three-dimensional network structure of the hydrogel provided by the present invention is constructed by secondary bonds such as hydrogen bonds formed between polymer chains through the interaction of positive and negative charges between negatively charged component A and positively charged component B. The hydrogel has self-healing properties and blood coagulation promoting function, which can shorten the blood coagulation time by 50%; it also has good strong adhesion and underwater adhesion performance, injectability, and guaranteed biocompatibility and safety, with tensile elasticity of up to 300%, adhesion strength to cowhide in air reaching 180kPa, and underwater adhesion strength exceeding 60kPa, and has good application prospects in making wound dressings and cell tissue adhesives. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0036] Figure 1 The self-healing process of the injectable hydrogel in Example 1 is shown.

[0037] Figure 2 The stretching process of the injectable hydrogel in Example 1 is shown.

[0038] Figure 3 The scanning electron micrograph of the injectable hydrogel in Example 2 is shown.

[0039] Figure 4 Schematic diagram showing the injection characteristics of the injectable hydrogel in Example 2.

[0040] Figure 5 A schematic diagram showing the adhesion strength of the injectable hydrogel in Example 2. DETAILED DESCRIPTION

[0041] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0042] Example 1

[0043] The preparation process of injectable hydrogel is as follows:

[0044] (1) Dissolve a certain amount of gelatin and polyethylene glycol by heating at 60°C;

[0045] (2) Adding negatively charged nanoclay to the solution obtained in step (1), stirring at room temperature and ultrasonically treating for 5 minutes to mix evenly, to obtain a stable solution, component A; the content of gelatin in component A is 3wt%, the content of polyethylene glycol is 1wt%, and the content of negatively charged nanoclay is 6wt%.

[0046] (3) Add a certain amount of polyacrylamide to ultrapure water, heat to dissolve, then add dopamine hydrochloride, CaCl2, and bacitracin zinc respectively, stir evenly, and obtain a stable solution, component B; the content of polyacrylamide in component B is 2wt%, the mass ratio of polyacrylamide, dopamine hydrochloride, and CaCl2 is 1:0.01:0.01, and the mass concentration of bacitracin zinc in component B is 50μg / mL.

[0047] (4) Component A and component B are mixed in a volume ratio of 2:1, shaken, and the mixed solution is rapidly solidified to obtain an injectable hydrogel.

[0048] Performance testing process:

[0049] (1) The obtained injectable hydrogel was subjected to an adhesion strength test, and the experimental result showed that its underwater adhesion strength was 65 kPa. (2) The injectable hydrogel obtained in (4) was subjected to a self-healing test, and the experimental result showed that after 10 seconds of self-healing, its self-healing rate was 90%. The specific self-healing process is as follows: Figure 1As shown, it can be seen that after the two cut hydrogels come into contact with each other, they can form a whole again after 10 seconds, and the formed whole still has good tensile elasticity.

[0050] (3) The obtained injectable hydrogel was subjected to a coagulation test. Compared with the blank group, the coagulation test time was shortened by 40%.

[0051] (4) The obtained injectable hydrogel was subjected to antibacterial experiments, and the results showed that it had good antibacterial properties against Staphylococcus aureus (99%) and Escherichia coli (95%).

[0052] (5) The obtained injectable hydrogel was subjected to a cell proliferation experiment. The results showed that it had a good effect in promoting cell proliferation. Compared with the blank control group without injectable hydrogel, the cell proliferation rate was about 110%.

[0053] (6) The obtained injectable hydrogel was subjected to a tensile elasticity test. The results are as follows Figure 2 As shown, the visible gel can be stretched to 300% of its length.

[0054] Example 2

[0055] The preparation process of injectable hydrogel is as follows:

[0056] (1) Dissolve a certain amount of gelatin and polyethylene glycol by heating at 60°C;

[0057] (2) Adding negatively charged nanoclay to the solution obtained in step (1), stirring at room temperature and ultrasonically treating for 5 minutes to mix evenly, to obtain a stable solution, component A; the content of gelatin in component A is 5wt%, the content of polyethylene glycol is 3wt%, and the content of negatively charged nanoclay is 4wt%.

[0058] (3) Add a certain amount of polyacrylamide to ultrapure water, heat to dissolve, then add dopamine hydrochloride, CaCl2, and ZnCl2 respectively, stir evenly, and obtain a stable solution, component B; the content of polyacrylamide in component B is 1wt%, the mass ratio of polyacrylamide, dopamine hydrochloride, and CaCl2 is 1:0.02:0.005, and the mass concentration of ZnCl2 in component B is 200μg / mL.

[0059] (4) Component A and component B are mixed in a ratio of 1:1, shaken, and the mixed solution is rapidly solidified to obtain an injectable hydrogel. The scanning electron microscopy image of the hydrogel is shown in FIG. Figure 3 As described above, an obvious polymer network structure can be seen, and nanoparticles are attached to the polymer chain. The injectable hydrogel of the present invention comprises component A and component B, which can form a hydrogel after mixing. The injection process is as follows: Figure 4 shown.

[0060] Performance testing process:

[0061] (1) The obtained injectable hydrogel was subjected to an adhesion strength test. The results are as follows Figure 5 As shown, the experiment measured that its adhesion strength to cow leather in dry air is 180kPa, its adhesion strength to cow leather in humid air is 120kPa, and its adhesion strength to cow leather underwater is more than 60kPa.

[0062] (2) The obtained injectable hydrogel was subjected to a self-healing test, and the experiment showed that after 10 seconds of self-healing, its self-healing rate was 95%.

[0063] (3) The obtained injectable hydrogel was subjected to a coagulation test. Compared with the blank group, the coagulation test time was shortened by 30%. Figure 6 shows the coagulation time.

[0064] (4) The obtained injectable hydrogel was subjected to antibacterial experiments, and the results showed that it had good antibacterial properties against Staphylococcus aureus (99%) and Escherichia coli (99%).

[0065] (5) The obtained injectable hydrogel was subjected to a cell proliferation experiment. The results showed that it had a good effect in promoting cell proliferation. Compared with the blank control group without injectable hydrogel, the cell proliferation rate was about 115%.

[0066] Example 3

[0067] The preparation process of injectable hydrogel is as follows:

[0068] (1) Dissolve a certain amount of gelatin and polyethylene glycol by heating at 55°C;

[0069] (2) Adding negatively charged nanoclay to the solution obtained in step (1), stirring at room temperature and ultrasonically treating for 5 minutes to mix evenly, to obtain a stable solution, component A; the content of gelatin in component A is 2wt%, the content of polyethylene glycol is 2wt%, and the content of negatively charged nanoclay is 6wt%.

[0070] (3) Add a certain amount of polyacrylamide to ultrapure water, heat to dissolve, then add dopamine hydrochloride, CaCl2, and bacitracin respectively, stir evenly, and obtain a stable solution, component B; the content of polyacrylamide in component B is 3wt%, the mass ratio of polyacrylamide, dopamine hydrochloride, and CaCl2 is 1:0.05:0.02, and the mass concentration of bacitracin in component B is 50μg / mL.

[0071] (4) Component A and component B are mixed in a ratio of 1:1, shaken, and the mixed solution is rapidly solidified to obtain an injectable hydrogel.

[0072] Performance testing process:

[0073] (1) The obtained injectable hydrogel was subjected to an adhesion strength test, and the experimental result showed that its underwater adhesion strength was 75 kPa.

[0074] (2) The injectable hydrogel was subjected to a self-healing test, and the experiment showed that after 10 seconds of self-healing, its self-healing rate was 98%.

[0075] (3) The obtained injectable hydrogel was subjected to a coagulation test. Compared with the blank group, the coagulation test time was shortened by 50%.

[0076] (4) The obtained injectable hydrogel was subjected to antibacterial experiments, and the results showed that it had good antibacterial properties against Staphylococcus aureus (96%) and Escherichia coli (90%).

[0077] (5) The obtained injectable hydrogel was subjected to a cell proliferation experiment. The results showed that it had a good effect in promoting cell proliferation. Compared with the blank control group without injectable hydrogel, the cell proliferation rate was about 120%.

[0078] Example 4

[0079] The preparation process of injectable hydrogel is as follows:

[0080] (1) heating a certain amount of agar and polyethylene glycol at 100°C to dissolve;

[0081] (2) Adding negatively charged nanoclay to the solution obtained in step (1), stirring at room temperature and ultrasonically treating for 5 minutes to mix evenly, to obtain a stable solution, component A; the content of agar in component A is 2wt%, the content of polyethylene glycol is 1wt%, and the content of negatively charged nanoclay is 6wt%.

[0082] (3) Add a certain amount of polyacrylamide to ultrapure water, heat to dissolve, then add dopamine hydrochloride, CaCl2(, and bacitracin respectively, stir evenly, and obtain a stable solution, component B; the content of polyacrylamide in component B is 3wt%, the mass ratio of polyacrylamide, dopamine hydrochloride, and CaCl2 is 1:0.02:0.005, and the mass concentration of bacitracin in component B is 100μg / mL.

[0083] (4) Component A and component B are mixed in a ratio of 1:1, shaken, and the mixed solution is rapidly solidified to obtain an injectable hydrogel.

[0084] Performance testing process:

[0085] (1) The obtained injectable hydrogel was subjected to an adhesion strength test, and the experimental result showed that its underwater adhesion strength was 190 kPa.

[0086] (2) The injectable hydrogel was subjected to a self-healing test, and the experiment showed that after 10 seconds of self-healing, its self-healing rate was 90%.

[0087] (3) The obtained injectable hydrogel was subjected to a coagulation test. Compared with the blank group, the coagulation test time was shortened by 30%.

[0088] (4) The obtained injectable hydrogel was subjected to antibacterial experiments, and the results showed that it had good antibacterial properties against Staphylococcus aureus (97%) and Escherichia coli (90%).

[0089] (5) The obtained injectable hydrogel was subjected to a cytotoxicity test, and the results showed that it was biocompatible.

[0090] Example 5

[0091] The preparation process of injectable hydrogel is as follows:

[0092] (1) heating a certain amount of carrageenan and polyethylene glycol at 70°C to dissolve;

[0093] (2) adding negatively charged nanoclay to the solution obtained in step (1), stirring at room temperature and ultrasonically treating for 5 minutes to mix evenly to obtain a stable solution, component A; the content of carrageenan in component A is 1wt%, the content of polyethylene glycol is 2wt%, and the content of negatively charged nanoclay is 5wt%.

[0094] (3) Add a certain amount of polyacrylamide to ultrapure water, heat to dissolve, then add dopamine hydrochloride, CaCl2, and AgNO3 respectively, stir evenly, and obtain a stable solution, component B; the content of polyacrylamide in component B is 1wt%, the mass ratio of polyacrylamide, dopamine hydrochloride, and CaCl2 is 1:0.03:0.015, and the mass concentration of AgNO3 in component B is 20μg / mL.

[0095] (4) Component A and component B are mixed in a ratio of 1:1, shaken, and the mixed solution is rapidly solidified to obtain an injectable hydrogel.

[0096] Performance testing process:

[0097] (1) The obtained injectable hydrogel was subjected to an adhesion strength test, and the experimental result showed that its underwater adhesion strength was 62 kPa.

[0098] (2) The injectable hydrogel was subjected to a self-healing test, and the experiment showed that after 10 seconds of self-healing, its self-healing rate was 90%.

[0099] (3) The injectable hydrogel was subjected to a coagulation test. Compared with the blank group, the coagulation test time was shortened by 45%.

[0100] (4) The obtained injectable hydrogel was subjected to antibacterial experiments, and the results showed that it had good antibacterial properties against Staphylococcus aureus (99.9%) and Escherichia coli (99.9%).

[0101] (5) The obtained injectable hydrogel was subjected to a cytotoxicity test, and the results showed that it was biocompatible.

[0102] Example 6

[0103] The preparation process of injectable hydrogel is as follows:

[0104] (1) Dissolving a certain amount of polypeptide and polyethylene glycol by heating at 60°C;

[0105] (2) Adding negatively charged nanoclay to the solution obtained in step (1), stirring at room temperature and ultrasonically treating for 5 minutes to mix evenly, to obtain a stable solution, component A; the content of the polypeptide in component A is 5wt%, the content of the polyethylene glycol is 2wt%, and the content of the negatively charged nanoclay is 10wt%.

[0106] (3) Add a certain amount of polyacrylamide to ultrapure water, heat to dissolve, then add dopamine hydrochloride, CaCl2, and bacitracin respectively, stir evenly, and obtain a stable solution, component B; the content of polyacrylamide in component B is 3wt%, the mass ratio of polyacrylamide, dopamine hydrochloride, and CaCl2 is 1:0.05:0.02, and the mass concentration of bacitracin in component B is 50μg / mL.

[0107] (4) Component A and component B are mixed in a ratio of 1:1, shaken, and the mixed solution is rapidly solidified to obtain an injectable hydrogel.

[0108] Performance testing process:

[0109] (1) The obtained injectable hydrogel was subjected to an adhesion strength test, and the experimental result showed that its underwater adhesion strength was 70 kPa.

[0110] (2) The obtained injectable hydrogel was subjected to a self-healing test, and the experiment showed that after 10 seconds of self-healing, its self-healing rate was 95%.

[0111] (3) The obtained injectable hydrogel was subjected to a coagulation test. Compared with the blank group, the coagulation test time was shortened by 50%.

[0112] (4) The obtained injectable hydrogel was subjected to antibacterial experiments, and the results showed that it had good antibacterial properties against Staphylococcus aureus (95%) and Escherichia coli (90%).

[0113] (5) The obtained injectable hydrogel was subjected to a cell proliferation experiment. The results showed that it had a good effect in promoting cell proliferation. Compared with the blank control group, the cell proliferation rate was about 115%.

[0114] Example 7

[0115] The preparation process of injectable hydrogel is as follows:

[0116] (1) heating a certain amount of sodium hyaluronate and polyethylene glycol at 50° C. to dissolve;

[0117] (2) Adding negatively charged nanoclay to the polymer solution obtained in step (1), stirring at room temperature and ultrasonically treating for 5 minutes to mix evenly to obtain a stable solution, component A; the content of sodium hyaluronate in component A is 2wt%, the content of polyethylene glycol is 1wt%, and the content of negatively charged nanoclay is 5wt%.

[0118] (3) Add a certain amount of polyacrylamide to ultrapure water, heat to dissolve, then add dopamine hydrochloride, CaCl2, and bacitracin respectively, stir evenly, and obtain a stable solution, component B; the content of polyacrylamide in component B is 2wt%, the mass ratio of polyacrylamide, dopamine hydrochloride, and CaCl2 is 1:0.03:0.01, and the mass concentration of bacitracin in component B is 50μg / mL.

[0119] (4) Solution A and solution B are mixed in a ratio of 1:2, shaken, and the mixed solution is rapidly solidified to obtain an injectable hydrogel.

[0120] Performance testing process:

[0121] (1) The obtained injectable hydrogel was subjected to an adhesion strength test, and the experimental result showed that its underwater adhesion strength was 60 kPa.

[0122] (2) The obtained injectable hydrogel was subjected to a self-healing test, and the experiment showed that after 10 seconds of self-healing, its self-healing rate was 95%.

[0123] (3) The obtained injectable hydrogel was subjected to a coagulation test. Compared with the blank group, the coagulation test time was shortened by 50%.

[0124] (4) The obtained injectable hydrogel was subjected to antibacterial experiments, and the results showed that it had good antibacterial properties against Staphylococcus aureus (95%) and Escherichia coli (90%).

[0125] (5) The obtained injectable hydrogel was subjected to a cytotoxicity test, and the results showed that it was biocompatible.

[0126] Example 8

[0127] The preparation process of injectable hydrogel is as follows:

[0128] (1) Dissolving a certain amount of zein and polyethylene glycol by heating at 60°C under alkaline conditions;

[0129] (2) Adding negatively charged nanoclay to the polymer solution obtained in step (1), stirring at room temperature and ultrasonically treating for 5 minutes to mix evenly, to obtain a stable solution, component A; the content of gelatin in component A is 0.5wt%, the content of polyethylene glycol is 1wt%, and the content of negatively charged nanoclay is 8wt%.

[0130] (3) Add a certain amount of polyacrylamide to ultrapure water, heat to dissolve, then add dopamine hydrochloride, CaCl2, and ZnCl2 respectively, stir evenly, and obtain a stable solution, component B; the content of polyacrylamide in component B is 1.5wt%, the mass ratio of polyacrylamide, dopamine hydrochloride, and CaCl2 is 1:0.03:0.01, and the mass concentration of ZnCl2 in component B is 100μg / mL.

[0131] (4) Solution A and solution B are mixed in a ratio of 1:1, shaken, and the mixed solution is rapidly solidified to obtain an injectable hydrogel.

[0132] Performance testing process:

[0133] (1) The obtained injectable hydrogel was subjected to an adhesion strength test, and the experimental result showed that its underwater adhesion strength was 68 kPa.

[0134] (2) The injectable hydrogel was subjected to a self-healing test, and the experiment showed that after 10 seconds of self-healing, its self-healing rate was 90%.

[0135] (3) The obtained injectable hydrogel was subjected to a coagulation test. Compared with the blank group, the coagulation test time was shortened by 40%.

[0136] (4) The obtained injectable hydrogel was subjected to antibacterial experiments, and the results showed that it had good antibacterial properties against Staphylococcus aureus (96%) and Escherichia coli (90%).

[0137] (5) The obtained injectable hydrogel was subjected to a cell proliferation experiment. The results showed that it had a good effect in promoting cell proliferation. Compared with the blank group without injectable hydrogel, the cell proliferation rate was about 105%.

[0138] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. An injectable hydrogel with self-healing and adhesive properties, characterized in that: The injectable hydrogel is generated by the interaction between component A and component B through positive and negative charges; Wherein, the component A is a negatively charged stable solution obtained by the reaction of natural polymer, polyethylene glycol and negatively charged nanoclay; the component B is a positively charged stable solution obtained by the reaction of polyacrylamide with dopamine hydrochloride, calcium chloride and antibacterial ingredients; The natural polymer is selected from one or more of gelatin, hyaluronic acid, silk fibroin, zein, agar, carrageenan, and alginate; In the component A, the mass proportion of natural polymer is 0.1-5 wt %, the mass proportion of polyethylene glycol is 0.1-5 wt %, and the mass proportion of negatively charged nanoclay is 1-10 wt %; The molecular weight of the polyacrylamide is 2 million to 14 million; The mass proportion of polyacrylamide in the B component is 1~5 wt%, and the mass ratio of polyacrylamide, dopamine hydrochloride and calcium chloride is 1:(0.01~1):(0.005~0.02).

2. The injectable hydrogel according to claim 1, characterized in that The volume ratio of component A to component B is 2:1 to 1:

2.

3. The injectable hydrogel according to claim 1, characterized in that The preparation process of the A component includes: heating and dissolving the natural polymer and polyethylene glycol, mixing and dissolving them in pure water, and then adding negatively charged nanoclay and mixing them to obtain the A component.

4. The injectable hydrogel according to claim 1, characterized in that The number average molecular weight of the polyethylene glycol is 0.8-100,000.

5. The injectable hydrogel according to claim 1, characterized in that The type of the nanoclay is selected from at least one of attapulgite nanoclay, halloysite nanoclay or hydrophilic bentonite, and the particle size of the nanoclay is 1-100 nm.

6. The injectable hydrogel according to claim 1, characterized in that The preparation process of the B component includes: dissolving polyacrylamide in pure water, adding dopamine hydrochloride, calcium chloride and antibacterial components, and mixing to obtain the B component.

7. The injectable hydrogel according to claim 1, characterized in that The antibacterial component is selected from one or more of bacitracin, bacitracin zinc, nisin, chitosan, ZnCl2, AgNO3, silver nanoparticles, and ZnO.

8. The injectable hydrogel according to claim 1, characterized in that The mass concentration of the antibacterial component in component B is 20 μg / mL ~ 200 μg / mL.

9. A method for preparing an injectable hydrogel having self-healing and adhesive properties as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: (1) The natural polymer and polyethylene glycol are heated and dissolved in pure water, and then negatively charged nanoclay is added and mixed to obtain component A; (2) dissolving polyacrylamide in pure water, adding dopamine hydrochloride, calcium chloride and antibacterial components, and mixing well to obtain component B; (3) Component A and component B are mixed in proportion, shaken, and cured to obtain an injectable hydrogel.

10. Use of the injectable hydrogel with self-healing and adhesive properties as claimed in any one of claims 1 to 8 in making wound dressings or cell tissue adhesives.

Citation Information

Patent Citations

  • Recombinant collagen injectable hydrogel and preparation method thereof

    CN112316214A